HIV and the gut microbiota: composition, consequences, and avenues for amelioration - Vujkovic-Cvijin, Ivan (Curr HIV/AIDS Rep, 2019)
PURPOSE OF REVIEW: We discuss recent advances in understanding of gut bacterial microbiota composition in HIV-infected subjects and comment on controversies. We discuss the putative effects of microbiota shifts on systemic inflammation and HIV disease progression and potential mechanisms, as well as ongoing strategies being developed to modulate the gut microbiota in humans for amelioration of infectious and inflammatory diseases. RECENT FINDINGS: Lifestyle and behavioral factors relevant to HIV infection studies have independent effects on the microbiota. Microbial metabolism of immunomodulatory compounds and direct immune stimulation by translocation of microbes are putative mechanisms contributing to HIV disease. Fecal microbiota transplantation, microbial enzyme inhibition, phage therapy, and rationally selected probiotic cocktails have emerged as promising strategies for microbiota modulation. SUMMARY: Numerous surveys of the HIV gut microbiota matched for lifestyle factors suggest consistent shifts in gut microbiota composition among HIV-infected subjects. Evidence exists for a complex pathogenic role of the gut microbiota in HIV disease progression, warranting further study.